ANALISIS FAKTOR KONFIRMATORI STRATEGI POSITIONING PASAR MODERN INDOMARET (Studi Kasus Wilayah Tembalang Kota Semarang) - Sholihin, Imam Nur; Mustafid, Mustafid; Safitri, Diah (Jurnal Gaussian, 2014)
Indomaret marketing strategy became one of modern market that has significant development in the last five years. Market positioning is one form of marketing strategy that functions to adjust as desired market position of market actors. Positioning has some major elements of the constituent factors of the product, price, place and promotion. Measurement of the magnitude of the influence of each factor were developed with confirmatory factor analysis. This study aims to examine the factors that influence the positioning strategy and the characteristics of the modern consumer market. The method used in the study using confirmatory factor analysis as used multivariate analysis to confirm the hypothesized model. The study was based on a case study on consumer Indomaret modern market in Tembalang, Semarang City. Results of the analysis showed that all the variables are valid and reliable indicators to measure the factors. Can be known as well as some consumer characteristics of a modern market. Among the interested consumer spending in the modern market with regard to the quality of the stuff is good, the existence of a clear price list, inventory as well as an interesting ad.